Les nouveaux moyens de paiement ont-ils besoin d'un cadre juridique spécifique : l'expérience française - Delahaie, Henri; Grissonnanche, André (Les Cahiers de droit, 1983)
Payment by delivery of a sum of money or by another common type of negotiable instrument is regarded in practice as an obsolete way of settling debts. It is being gradually replaced by a product of modern technology often called « electronic money ». This phenomenon may call for a new juridical framework. Serious consideration is given to the matter in the following article which, in the process, affords us a glimpse of its treatment under French law.